Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/cncr.30319
|View full text |Cite
|
Sign up to set email alerts
|

The health care experience of patients with cancer during the last year of life: Analysis of the SEER‐CAHPS data set

Abstract: Among patients with cancer within 1 year before death, experience with health plans, physicians, and medical care were found to be associated with sociodemographic, insurance, and clinical characteristics. These findings provide guidance for the development of programs to improve the experience of care among individuals with cancer. Cancer 2017;123:336-344. © 2016 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“… 4 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 These studies showed that overall, younger patients reported less positive experiences than older ones, 20 , 22 , 24 females reported less positive experiences than males, 20 and non-white patients reported less positive experiences than those from the white population. 4 , 20 , 22 , 29 Similar variation in cancer patients’ experiences by their sex, age, and ethnicity were also found in studies from USA, 30 , 31 , 32 and Canada. 33 …”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“… 4 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 These studies showed that overall, younger patients reported less positive experiences than older ones, 20 , 22 , 24 females reported less positive experiences than males, 20 and non-white patients reported less positive experiences than those from the white population. 4 , 20 , 22 , 29 Similar variation in cancer patients’ experiences by their sex, age, and ethnicity were also found in studies from USA, 30 , 31 , 32 and Canada. 33 …”
Section: Resultssupporting
confidence: 70%
“…The number of negative comments about care experiences varied by gender, age, employment status, and cancer type. Halpern et al., 2017 31 The health care experience of patients with cancer during the last year of life: Analysis of the SEER-CAHPS data set Cross-sectional study using the SEER- CAHPS data between 1998 and 2011 for patients with all cancer types in the dataset To assess factors influencing cancer patients’ experiences among individuals within one year before death. 1 Patients with higher general or mental health status were significantly more likely to report excellent experiences across all the measures examined.…”
Section: Resultsmentioning
confidence: 99%
“…12 The possibility of an association between patient experience and survival has not often been investigated in a cancer care setting. Sociodemographic and systemic variations in patient experience with cancer care have been documented in several studies from the United States 13,14 and England. [15][16][17][18][19] Some of the factors associated with poorer experience such as lower socioeconomic status are also associated with poorer outcomes raising the question of whether an independent association exists between patients' experiences of cancer care and their survival.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular diagnostics supported by genomic profiling allow applied novel targeted therapies to effectively treat patients, tailoring the treatment to target their unique tumor characteristics (Al-Rohil et al, 2016). Several patient surveys, including Patient Reported Experience Measures (PREMs), have been developed to identify priorities of patient experiences and preferences (Weldring and Smith, 2013; Taylor et al, 2015; Tremblay et al, 2015; Windham et al, 2015; Burns et al, 2016; Halpern et al, 2016). Alongside this gradual shift toward personalized medicine, importance of patient engagement is also increasingly recognized (Tremblay et al, 2015; King et al, 2016; Schnipper et al, 2016).…”
Section: Introductionmentioning
confidence: 99%